Answer:
c = 2
Step-by-step explanation:
6c + 3y = 18
6c + 3(2) = 18
6c + 6 = 18
6c = 12
c = 2
Answer: 629.44
Step-by-step explanation:
562 times .2 = 112.4 that’s the 20% discount. 562-112.4 = 449.6 times 1.4 = 629.44
Answer: 34
Step-by-step explanation:
<u>Given expression</u>
[3 - (3 · 3) + 33 ÷ 3] × 4 · 5 / 10 - 2 · 3
<u>Simplify by parentheses in the bracket</u>
=[3 - 9 + 33 ÷ 3] × 4 · 5 / 10 - 2 · 3
<u>Simplify by multiplication</u>
=[3 - 9 + 33 ÷ 3] × 20 / 10 - 6
<u>Simplify by division</u>
=[3 - 9 + 11] × 10 - 6
<u>Simplify by bracket (addition/subtraction)</u>
=[-6 + 11] × 10 - 6
=[4] × 10 - 6
<u>Simplify by multiplication</u>
=40 - 6
<u>Simplify by subtraction</u>
=![\boxed{34}](https://tex.z-dn.net/?f=%5Cboxed%7B34%7D)
Hope this helps!! :)
Please let me know if you have any questions
$52.95 - $2.50 = $50.45
$50.45 divided by 5 (number of people) = $10.09 per person
Which of the following statements correctly describes the expression below based on its degree and number of terms? 3x^4 - 7x^2 + 11. The expression has four terms and a degree of 6. The expression is a trinomial with a degree of 6. The expression is a trinomial with a degree of 4. The expression has four terms and a degree of 4.
hope this helps!